The observation protocol for academic literacies : a tool for building expertise for teachers of English learners - Lavadenz, Magaly C.; Armas, Elvira G., 1967- (Bristol ; Jackson : Multilingual Matters, 2024)
"This book presents a validated observation instrument to support and develop the pedagogic expertise of teachers of English Learners in US schools. With real examples of classroom observations, it offers teachers, researchers and policymakers a tool for professional development, classroom research and program improvement"--
Intro -- Cover -- Half-Title -- Series -- Title -- Copyright -- Contents -- Acknowledgments -- 1 Building Expertise for Teachers of English Learners: Introduction to the Observation Protocol for Academic Literacies (OPAL) Instrument -- 2 Seeing What’s There: Sharpening Our Observation Skills -- 3 OPAL Domain 3: Comprehensibility -- 4 OPAL Domain 4: Interactions -- 5 OPAL Domain 1: Rigorous and Relevant Curriculum -- 6 OPAL Domain 2: Connections -- 7 Using the OPAL for Professional Learning, Research and Evaluation Purposes -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Appendix E -- Appendix F -- Appendix G -- References -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 07, 2024).
JSTOR
Keywords: English language -- Study and teaching; English teachers -- Training of; Observation (Educational method); Anglais (Langue) -- Étude et enseignement; Observation (Méthode d'enseignement); LANGUAGE ARTS & DISCIPLINES / Study & Teaching; English language -- Study and teaching; English teachers -- Training of; Observation (Educational method)